Integrating Pancasila Ethics in Leadership in the VUCA Era - Sanipar, Sanipar (Jurnal Civicus, 2023)
The purpose of this research is to examine the urgency of Pancasila ethics in leadership in the VUCA era. This research is qualitative research with a literary approach. Researchers conducted a literature review of various literature based on keywords appropriate to the research study. The research steps are as follows: 1) Determining keywords based on the focus of the research study; 2) Search for literature via Google Scholar then reduce it, analyze it and draw conclusions according to the research focus. Leaders who have the Pancasila ethic will always adhere to the values of divinity, humanity, unity, people and social justice, which are universal values and are needed in every era, including in facing the current VUCA era. Integrating Pancasila leadership ethics in the VUCA era can include; a) integrating character education based on Pancasila values in every curricular and extracurricular learning; b) building leadership skills with project-based learning that is directly related to overcoming problems that occur in the community; c) cultivating digital citizenship literacy to build abilities in managing various information, so as to gain positive global insights and filter out negative impacts; d) Making the educational environment a democratic laboratory that promotes a space for self-actualization that is inclusive, collaborative and stimulates the development of various responsible leadership skills.